Formulation of Framework for Evacuation of Tsunami Disaster after COVID-19 Pandemic on The South Coast of Watulimo, Trenggalek - Fadhilatus Shoimah; Fadly Usman; Septiana Hariyani (Diponegoro University, 2022)
The research aims to identify and design the latest theory-based tsunami disaster evacuation after the COVID-19 pandemic. Analysis of temporary shelters and analysis of evacuation routes were used in research with scoring techniques and network analysis techniques. The conceptual framework related to tsunami disaster evacuation after the COVID-19 pandemic has been compiled in research and can be used as material for consideration to formulate government policies and determine contingency plans and operational plans that will be carried out in the event of a tsunami disaster following the COVID-19 pandemic. Parameters of temporary shelter variables that must be considered are building function, the number of floors, building capacity, road location, building area, distance from the beach, and building construction. The capacity of the temporary shelter before the COVID-19 pandemic was obtained from the building area divided by the minimum space requirement per person of 1.64 m2. After the COVID-19 pandemic, the minimum space requirement per person combined with a physical distance of 2 m, the total area required will be 6 m2/person. Meanwhile, the parameters of the evacuation route variables that must be considered are road width, travel time, road pavement conditions, and road class.